PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR “MY MONEY” UNTUK PENGENALAN LITERASI KEUANGAN PADA KELOMPOK B DI RA MAMBAUL HIKMAH DESA GIRIMOYO KECAMATAN KARANGPLOSO KABUPATEN MALANG: DEVELOPMENT OF THE PICTURE STORYBOOK “MY MONEY” AS A FINANCIAL LITERACY INTRODUCTION FOR GROUP B CHILDREN AT RA MAMBAUL HIKMAH, GIRIMOYO VILLAGE, KARANGPLOSO DISTRICT, MALANG REGENCY - Faizah, Zulfa Hanifil; Sulyandari, Ari Kusuma; Setiawan, Eko (Universitas Islam Malang, 2022)
This research is entitled Development of Learning Media for Introduction to Financial Literacy in Group B at Ra Mamba'ul Hikmah, Girimoyo Village, Karangploso District, Malang Regency. The background of this research is about the introduction of financial literacy in early childhood which does not yet exist, so it is necessary to introduce this financial literacy through the development of learning media in the form of picture story books. This study uses the borg and gall development research model. Development data were obtained through interviews and observations at RA Mamba'ul Hikmah, Girimoyo Village, Karangploso District, Malang Regency and from the results of trials in small groups and large groups through questionnaires and also observation activities during the activity. The results of the initial research at RA Mamba'ul Hikmah, Girimoyo Village, Karangploso District, Malang Regency, obtained qualitative data results involving teachers who are experts in the field of learning and media. The result is that children aged include the three aspects, namely, Cognitive, Affective, and Psychomotor in learning financial literacy. The results of quantitative data obtained from the results of the small group test and large group test, obtained 75% results from statistical data which include convenience, pleasure, and safety.